Development, implementation and evaluation of pictorial health education for low-literacy, low-resource communities - Barrett, Jeremy Christopher (Curtin University, 2017)
Rural and remote communities often face significant challenges to maintaining their health and well-being. Existing health education materials distributed within such communities are often presented in a traditional written format, making them inaccessible to people with low literacy levels. Evidence supports an alternative approach to communicating health promotion messages using picture-based materials rather than the conventional written formats. This research assessed the effectiveness of a cartoon-based pictorial educational tool to communicate key messages about hygiene.